2013
DOI: 10.1016/j.psyneuen.2012.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early life social stress on maternal behavior and neuroendocrinology

Abstract: Maternal mood disorders such as depression and chronic anxiety can negatively affect the lives of both mothers and their adult offspring. An active focus of maternal depression and anxiety research has been the role of chronic social stress in the development of these disorders. Chronic exposure to social stress is common in humans, especially in lactating mothers, and postpartum mood disorders have been correlated with high levels of social conflict and low levels of social support. Recent studies have descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
105
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(124 citation statements)
references
References 70 publications
14
105
3
2
Order By: Relevance
“…Both the maternal care and offspring data indicate that CSS may have enduring effects on the future generations, and research on the effects of chronic stress on maternal behavior support the hypothesis that the effects of chronic stress on maternal behavior are hormonally mediated (Murgatroyd and Nephew 2012). Furthermore, recent data from the adult female offspring of stressed dams supports the hypothesis that CSS as a form of early life stress causes changes in central oxytocin (OXT) and prolactin (PRL) which are associated with inefficient nursing behavior 12 . The CSS model complements other effective models of stress induced disruptions in maternal behavior, such as limiting nesting material 26,27 and maternal separation 28,29 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Both the maternal care and offspring data indicate that CSS may have enduring effects on the future generations, and research on the effects of chronic stress on maternal behavior support the hypothesis that the effects of chronic stress on maternal behavior are hormonally mediated (Murgatroyd and Nephew 2012). Furthermore, recent data from the adult female offspring of stressed dams supports the hypothesis that CSS as a form of early life stress causes changes in central oxytocin (OXT) and prolactin (PRL) which are associated with inefficient nursing behavior 12 . The CSS model complements other effective models of stress induced disruptions in maternal behavior, such as limiting nesting material 26,27 and maternal separation 28,29 .…”
Section: Introductionmentioning
confidence: 88%
“…Recent rodent studies have been focusing on the use of ethologically relevant stressors, such as chronic social stress (CSS), in the study of the effects of stress on offspring behavior and mood disorders [9][10][11][12][13] . In an effort to develop an ethological model for postpartum depression, reduce the physiological component of the stressor used, and generate consistent behavioral and physiological results, our lab has focused on the use of social stress.…”
Section: Introductionmentioning
confidence: 99%
“…Rats stressed during prenatal life show similar behavioral and endocrine programming [154]. Several animal studies have demonstrated the important modifiable reflects of early maternal behaviors [45, 155158]. Notably, changes in maternal care, through CSS, lead to altered neuropeptide regulation in the PVN and SON [45].…”
Section: Ppd and Anxiety As A Risk Factor For Depression And Anxiementioning
confidence: 99%
“…Several animal studies have demonstrated the important modifiable reflects of early maternal behaviors [45, 155158]. Notably, changes in maternal care, through CSS, lead to altered neuropeptide regulation in the PVN and SON [45]. Meaney and colleague’s studies have linked increased arch back nursing, and licking and grooming to enhanced HPA axis feedback regulation and reduced anxiety-related behavior through increased glucocorticoid receptor (GR) expression in the hippocampus [159].…”
Section: Ppd and Anxiety As A Risk Factor For Depression And Anxiementioning
confidence: 99%
“…Роль стресса раннего периода жизни в патогенезе аутизма, депрессии и хронической нейродегенерации в настоящее время активно обсуждается [43], а отде-ление потомства от матери является адекватной экс-периментальной моделью депрессии [44], причем такой вид стресса оказывает влияние не только на развитие потомства в отдаленном периоде жизни, но и на состоя-ние матери. На экспериментальных моделях убедительно показано, что отделение потомства от матери приводит к значительным колебаниям содержания ОТ в гипота-ламусе, миндалине мозга, однако нельзя не принимать во внимание то, что краткосрочные периоды отделения от матери могут иметь и позитивный поведенческий результат в отдаленные периоды жизни [1].…”
unclassified